A PRAGMATIC ANALYSIS OF THE FLOUTING MAXIMS IN KICK ANDY TALK SHOW: “LASKAR PELANGI” BASED ON GRICE’S COOPERATIVE PRINCIPLE - Evidoyanti .; Siti Kustini (INTEKNA informasi teknik dan niaga, 2012)
The present study addresses the issue of flouting maxims in talk show conversations viewed from a Gricean perspective. Conversations in Kick Andy talk show; “Laskar Pe-langi” were analyzed with regard to acts of flouting of Grice’s maxims. The qualitative da-ta of the study gave evidence that three out of four Gricean maxims were flouted. The most frequently maxim flouted encountered was the maxim of quantity (71.42%); the se-cond maxim flouted was the maxim of relevance (61.90%); and the least frequent maxim flouted was the maxim of manner (42%). Giving long-winded responses, changing the topic of the conversation abruptly, giving too much information than the situations requir-ed, and lacking of ability to interpret the questions were considered to be the causal fac-tors of the speakers’ failure in fulfilling the maxims.